2021
DOI: 10.1038/s41598-021-82600-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent alterations in behavior, drug responses and dopamine transporter expression in heterozygous DAT-Cre mice

Abstract: Heterozygous mice that express Cre-recombinase under the dopamine transporter promoter (DAT-Cre knock in mice, or KI) are widely used for targeting midbrain dopamine neurons, under the assumption that their constitutive physiology is not affected. We report here that these mice display striking sex-dependent behavioral and molecular differences in relation to wildtypes (WT). Male and female KI mice were constitutively hyperactive, and male KI mice showed attenuated hyperlocomotor responses to amphetamine. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 79 publications
2
11
0
Order By: Relevance
“…We tested DAT-IRES-Cre mice for comparison ( Figures S2H – S2K ) and did find a small but significant increase in locomotor activity and a decrease in grooming time in heterozygous mice compared with WT littermate controls. These results are consistent with recent reports showing behavioral alterations in DAT-IRES-Cre mice, including hyperactivity ( Chohan et al, 2020 ; Costa et al, 2021 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We tested DAT-IRES-Cre mice for comparison ( Figures S2H – S2K ) and did find a small but significant increase in locomotor activity and a decrease in grooming time in heterozygous mice compared with WT littermate controls. These results are consistent with recent reports showing behavioral alterations in DAT-IRES-Cre mice, including hyperactivity ( Chohan et al, 2020 ; Costa et al, 2021 ).…”
Section: Resultssupporting
confidence: 93%
“…Here, we did not find any changes in gross locomotor activity in DAT-P2A-Flpo heterozygous mice; however, testing in other behavioral contexts is warranted prior to using this line for different experiments. Notably, several recent studies have reported sex-dependent changes in motor and psychostimulant-induced behaviors in DAT-IRES-Cre mice ( Costa et al, 2021 ; Chohan et al, 2020 ). We recommend designing experiments so that all mice are heterozygous for DAT-P2A-Flpo and thus have similar DAT expression, and avoid comparing DAT-P2A-Flpo heterozygotes directly with WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Because gene knock-ins and transgene insertions can cause unintended changes in native gene expression and function ( 86 91 ), we evaluated the impact of 1) the Slc1a1 -tetO operator, and 2) the Th- tTA transgene independent of the Slc1a1 -tetO operator in mice that were administered regular chow. While mice that were homozygous for the Slc1a1 -tetO allele ( Slc1a1 -tetO homo / Th -tTA-) displayed ~50% reduction in EAAT3 expression compared to WT mice ( Supplementary Figure S5B ), they did not show significant differences in AMPH-induced responses or basal dopaminergic transmission ( Supplementary Figure S5C – M ).…”
Section: Resultsmentioning
confidence: 99%
“…In this species, the only alternative driver line is a TH-cre line (which -in contrast to mice -has been reported to be reliable both in terms of efficacy, and in terms of specificity) 18,57 . Finally, the PRS×8 system circumvents common pitfalls of cre driver lines, such as phenotypic alterations, which have been vastly reported for neuromodulatory mouse lines [58][59][60] . In sum, all available model systems offer unique features to elucidate different aspects of LC function.…”
Section: Discussionmentioning
confidence: 99%